Synthesis and biological evaluation of novel imidazopyrimidin‐3‐amines as anticancer agents. (29th December 2016) - Mahdavi, Mohammad; Dianat, Shima; Khavari, Behnaz; Moghimi, Setareh; Abdollahi, Mohammad; Safavi, Maliheh; Mouradzadegun, Arash; Kabudanian Ardestani, Sussan; Sabourian, Reyhaneh; Emami, Saeed; Akbarzadeh, Tahmineh; Shafiee, Abbas; et al.
Abstract : Groebke–Blackburn–Bienayme reaction has been utilized for the synthesis of new imidazo[1, 2‐ a ]pyrimidine derivatives as novel anticancer agents. The cytotoxic activities of compounds were evaluated against human cancer cell lines including MCF‐7, T‐47D, and MDA‐MB‐231, compared with etoposide as the standard drug. Among the tested compounds, hydroxy‐ and/or methoxy‐phenyl derivatives (6a–c and6k ) with IC50 values of 6.72–14.36 μm were more potent than etoposide against all cell lines. The acridine orange/ethidium bromide double staining and DNA fragmentation studies demonstrated that the cytotoxic effect of 3‐hydroxy‐4‐methoxyphenyl derivative6c is associated with apoptosis in cancer cells. Abstract : A series of imidazo[1, 2‐ a ]pyrimidines6a–o were synthesized as novel anticancer agents. Some of them were more potent than etoposide. Particularly, compound6c was fivefold more potent than etoposide against T‐47D cells (IC50 = 6.72 μm ).